Stem Cells, Biomarkers and Genetic Profiling: Approaching Future Challenges in Urology. Issue 1 (January 2016) - Mancini, Mariangela; Zazzara, Michele; Zattoni, Filiberto
Urological research is facing future challenges, the most difficult one is the fast and meaningful transfer of the massive amount of data from research basic to clinical practice. Between the most important issues that research should focus in the next years are targeting of tumor stem cells, clinical application of biomarkers, and wide application of genetic profiling of urological neoplasms. Several clinical implications are expected, from diagnosis to selection of candidates for different treatment modalities, to modulation of sequential treatment plans, to prognosis. A number of clinical trials based on research data from the hottest issues are in the pipeline. In this review, we will focus on new insights from recent work worlwide in urological research, with particular attention to high-risk nonmuscle-invasive and muscle-invasive bladder cancer, prostate cancer, and kidney cancer. Cancer care is moving towards a personalized approach in patient management. The most important issues in urological research point strongly in this direction and show an enormous potential for the rapid landing of Urology in the era of personalized medicine.